Comparing Effectiveness Between Rubric and Traditional Methods to Assess Clinical Practice among Vietnamese Nursing Students: A Quasi-Experimental Study - Dao Dieu Nguyen, Trang; Duong Thi Ngoc, Lan; Nguyen Thi Phuong, Thao; Tran Thi, Nguyet; Nguyen Thi Thanh, Thanh; Vo Thi Diem, Binh; Vo Thanh, Ton; Nguyen Thi, May; Hoang Thi, Hien; Ton Nu Minh, Duc; Hoang Thi Phuong, Thao (Pacific Rim International Journal of Nursing Research, 2024)
Assessing student competency in clinical practice poses a significant challenge for nursing educators. Rubrics are assessment tools to mitigate subjective biases and lay out set standards and criteria to assess performance, assignment or behavior. The rising enrollment of nursing students at the University of Medicine and Pharmacy, Hue University indicates a shift in healthcare education, but the health system’s slow adaptation presents challenges. Current assessment methods lack a unified standard, leading to inconsistencies in measuring nursing competencies. A standardized assessment framework is urgently needed to improve education quality and prepare students for national certification exams, yet evaluations of effectiveness in Vietnam remain unexamined. This quasi-experimental study aimed to compare the effectiveness of rubrics and traditional methods in assessing student competency in clinical practice on self-confidence, satisfaction with clinical teaching, and academic results among nursing students studying a module on women’s health, mothers, families, and nursing care. Purposive sampling was employed to select 186 nursing students at the University of Medicine and Pharmacy, Hue University, with 89 students in the rubric group and 97 students in the traditional group. Data collection tools included the Demographic Characteristics, Self-perceived Confidence, Undergraduate Nursing Student Academic Satisfaction Scale, and Rubric and Traditional Assessment. The results of the study demonstrated that students in the rubric group exhibited significantly higher mean scores across several important dimensions, including overall confidence, satisfaction with clinical teaching, and learning performance when compared to their counterparts in the traditional group. However, the rubric group did not report a statistically significant increase in perceptions regarding instructors being “approachable and comfortable about asking questions,” nor in demonstrating a “high level of knowledge and clinical expertise.” We concluded that the implementation of a rubric-based assessment approach positively influences students’ perceptions of their abilities and contributes to a more effective learning environment than the traditional method. Therefore, we consider that the rubric method should be used to evaluate the quality of nursing practice training with further testing widely in other groups of students, nursing courses, and other settings.